TCM and related active compounds in the treatment of gout: the regulation of signaling pathway and urate transporter - Sun, Xin; Yang, Le; Sun, Hui; Sun, Ye; Wei, Shuyun; Han, Ying; Wang, Wenkai; Kong, Ling; Wang, Xijun (Frontiers in Pharmacology, 2023)
Gout represents a metabolic ailment resulting from the accumulation of monosodium urate crystals within joints, causing both inflammation and, harm to tissues. The primary contributor to gout’s emergence is an elevated presence of serum urate, which is under the regulation of kidney and, gut urate transporters. Mitigating this risk factor is crucial for averting gout’s onset. Several treatments rooted in TCM and related active compounds have demonstrated efficacy in managing gout, skillfully regulating serum uric acid (UA) levels and curbing inflammation’s progression. This analysis compiles key foundational research concerning the molecular signaling pathways and UA transporters linked to gout, under the regulation of TCM. The focus includes individual botanical drug, active compounds, and TCM formulations, which have been consolidated and examined in this overview. The primary keywords chosen were “gout, hyperuricemia, gouty arthritis, traditional Chinese medicine, Chinese botanical drug, medicinal botanical drug, and natural plant”. Various relevant literatures published within the last 5 years were gathered from electronic databases, including PubMed, Web of Science, CNKI, and others. The findings revealed that TCM has the capacity to modulate various signaling pathways, including MAPK, NF-κB, PI3K/Akt, NLRP3 and JAK/STAT. Additionally, it impacts UA transporters like URAT1, GLUT9, ABCG2, as well as OATs and OCTs, thereby contributing to gout treatment. TCM helps maintain a balanced inflammatory interaction and facilitates UA excretion. This study enhances our understanding of TCM’s anti-gout mechanisms and introduces novel perspectives for establishing the clinical significance and future prospects of TCM-based gout treatment.